2019
DOI: 10.3758/s13414-019-01781-w
|View full text |Cite
|
Sign up to set email alerts
|

Bringing action into the picture. How action influences visual awareness

Abstract: This article discusses how the analysis of interactions between action and awareness allows us to better understand the mechanisms of visual awareness. We argue that action is one of several factors that influence visual awareness and we provide a number of examples. We also discuss the possible mechanisms that underlie these influences on both the cognitive and the neural levels. We propose that action affects visual awareness for the following reasons: (1) it serves as additional information in the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…The past years have seen a growing interest in elucidating the sources of information that contribute to confidence judgments, as a window into potential computational processes that allow the brain to monitor itself. Converging evidence from very different experimental paradigms suggested that confidence is modulated by motor information concurrent with the first-order response (Faivre et al, 2017;Fleming et al, 2015;Patel et al, 2012;Pereira et al, 2018); for a review see (Anzulewicz, Hobot, Siedlecka, & Wierzchoń, 2019). Here, we set out to directly investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The past years have seen a growing interest in elucidating the sources of information that contribute to confidence judgments, as a window into potential computational processes that allow the brain to monitor itself. Converging evidence from very different experimental paradigms suggested that confidence is modulated by motor information concurrent with the first-order response (Faivre et al, 2017;Fleming et al, 2015;Patel et al, 2012;Pereira et al, 2018); for a review see (Anzulewicz, Hobot, Siedlecka, & Wierzchoń, 2019). Here, we set out to directly investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The past years have seen a growing interest in elucidating the sources of information that contribute to confidence judgments, as a window into potential computational processes that allow us to monitor our own thoughts. Converging evidence from very different experimental paradigms suggested that confidence is modulated by motor information concurrent with the first-order response (Baranski & Petrusic, 1995, 1998Fetsch, Kiani, Newsome, & Shadlen, 2014;Kiani, Corthell, & Shadlen, 2014;Moran, Teodorescu, & Usher, 2015;Ratcliff & Starns, 2013;Vickers & Packer, 1982;Douglas Vickers, Burt, Smith, & Brown, 1985;Zylberberg, Fetsch, & Shadlen, 2016, For a review see Anzulewicz et al, 2019). Here, we set out to directly investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…These studies' authors suggested that carrying out a behavioral response acts as an additional source of evidence for metacognitive judgments. Following this, Anzulewicz et al (2019) listed four possible mechanisms through which action planning or execution could influence reported awareness. They point to possible (1) indirect effects that stem from motor cortex activity that affects cognitive processing, (2) perceptual evidence accumulation being influenced by attentional engagement, (3) enhancement of performance monitoring, and (4) integration of additional (including post-perceptual) evidence with the evidence accumulation process.…”
Section: Introductionmentioning
confidence: 99%